Preparation method of cellulose melamine resin composite material
By introducing modified cellulose into melamine resin and grafting using acylchlorotriazine diphenylsulfone polymer, the problem of insufficient mechanical strength and heat resistance of melamine resin materials is solved, and the cellulose density is significantly improved Bending strength, impact strength and heat resistance of amine resin composites.
Patent Information
- Application Number
- CN202411533547.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Melamine resin materials have shortcomings in terms of mechanical strength and heat resistance, especially the low bending strength and impact strength, which are difficult to meet certain application needs.
By introducing modified cellulose into the melamine resin and polymerizing with 4,4'-dihydroxydiphenylsulfone and phenylalanyl chloride homotriazine, an acyl chloride homotriazine diphenylsulfone polymer was obtained. Branches onto microcrystalline cellulose, blended with melamine resin, and heat-pressed to form a cellulose melamine resin composite material.
The bending strength, impact strength and heat resistance of cellulose melamine resin composite material are significantly improved, the thermal decomposition temperature of T5% and T10% of the material is increased, and the mass residual rate is improved.
Smart Images

Figure BDA0005111731580000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of melamine resins, in particular to a method for preparing a cellulose melamine resin composite material. Background Art
[0002] Melamine resin is a new type of polymer resin material obtained by polymerization reaction of melamine and formaldehyde as raw materials. It has high chemical activity, fast curing speed, high bonding strength, good water resistance and excellent wear resistance. It is widely used in furniture, automobiles, building materials and other fields. However, melamine resin has high curing crosslinking density, high brittleness and poor toughness. The toughening modification of melamine resin is a research hotspot. Cellulose, as a natural green environmentally friendly material with excellent mechanical properties, is widely used in the toughening modification of polymer materials. The invention patent with announcement number CN113980421 B discloses an environmentally friendly melamine powder material and its preparation method. Nanocrystalline cellulose, sodium periodate, 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, 2,2-dihydroxymethylbutyric acid, dibutyltin oxide and the like are used as raw materials to prepare modified nanocrystalline cellulose, which is then mixed with melamine resin to obtain melamine powder with the characteristics of heat resistance and water resistance. However, the melamine powder material of the patent does not have good mechanical properties such as bending strength and impact strength. Summary of the invention
[0003] The technical problem solved by the invention is: to provide a method for preparing a cellulose melamine resin composite material, and to improve the mechanical strength and heat resistance of the melamine resin.
[0004] The technical solution provided by the present invention is: a method for preparing a cellulose melamine resin composite material, comprising the following steps:
[0005] Step (1), adding triethylamine, 4,4'-dihydroxydiphenyl sulfone, and phenylalanyl chloride-s-triazine to N,N-dimethylformamide, stirring and reacting at room temperature for 18-24 hours, then adding phenylalanyl chloride-s-triazine, reacting for 2-3 hours, adding acetone to the solution, filtering, washing with acetone, and drying to obtain a chloride-s-triazine diphenyl sulfone polymer.
[0006] Step (2), adding microcrystalline cellulose to N,N-dimethylformamide, stirring, adding acyl chloride-s-triazine diphenyl sulfone polymer and triethylamine, filtering after reaction, washing with water and ethanol in turn, and drying to obtain modified cellulose.
[0007] Step (3), adding melamine resin and modified cellulose in a mass ratio of 100:(20-40) into an internal mixer for mixing, discharging the material, ball milling the material, and placing the material in a flat vulcanizer for hot pressing to obtain a cellulose melamine resin composite material.
[0008] Furthermore, in step (1), the molar ratio of triethylamine, 4,4'-dihydroxydiphenyl sulfone, and phenylalanyl chloride-s-triazine is (1.5-1.8):1:(0.7-0.74).
[0009] Furthermore, in step (2), the microcrystalline cellulose is stirred and then added with acyl chloride-based s-triazine diphenyl sulfone polymer and triethylamine in a mass ratio of 1:(0.2-0.5):(0.03-0.08).
[0010] Furthermore, the reaction in step (2) is carried out at room temperature for 6-10 hours.
[0011] Furthermore, in step (3), the temperature during mixing in the internal mixer is 70-80° C., and the mixing time is 30-60 min.
[0012] Furthermore, in step (3), the temperature during hot pressing in the flat vulcanizing machine is 150-165° C., the pressure is 15-20 MPa, and the time is 5-8 min.
[0013] Furthermore, the preparation method of phenylalanyl chloride-s-triazine comprises: adding DL-phenylalanine, N,N-diisopropylethylamine, and cyanuric chloride in a molar ratio of (3-3.3):(6-6.6):1 to tetrahydrofuran or 1,4-dioxane solvent, heating to 60-85°C in a nitrogen atmosphere, reacting for 12-18 hours, distilling under reduced pressure, recrystallizing the crude product with ethanol, adding the crystalline product to thionyl chloride, heating to 60-70°C, reacting for 3-5 hours, distilling under reduced pressure, and drying to obtain phenylalanyl chloride-s-triazine.
[0014] The technical effect of the present invention is as follows: the present invention utilizes 4,4'-dihydroxydiphenyl sulfone and phenylalanyl chloride-s-triazine to carry out polymerization reaction to obtain acyl chloride-s-triazine diphenyl sulfone polymer, the terminal acyl chloride group of which reacts with the hydroxyl group of microcrystalline cellulose, thereby grafting the s-triazine diphenyl sulfone polymer into the matrix of microcrystalline cellulose, and then blending with melamine resin, hot pressing and molding, to obtain a cellulose melamine resin composite material.
[0015] The diphenyl sulfone polymer containing a triazine structure introduced into the cellulose microcrystals of the present invention has good compatibility with the melamine resin containing a triazine structural unit, improves the dispersibility of the cellulose microcrystals in the melamine resin, and makes the cellulose microcrystals play a good reinforcing role, and the bending strength and impact strength of the melamine resin material are significantly improved. In addition, the introduction of the heat-resistant diphenyl sulfone structure increases the T 5% , T 10% The mass surplus rate also increases significantly, improving the heat resistance. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be arbitrarily combined with each other without conflict.
[0017] Example 1
[0018] To 20 mL of 1,4-dioxane solvent, add 15 mmol DL-phenylalanine, 30 mmol N,N-diisopropylethylamine, and 5 mmol cyanuric chloride, heat to 85 ° C in a nitrogen atmosphere, react for 12 hours, and distill under reduced pressure. The crude product is recrystallized from ethanol, and the crystalline product is added to 120 mmol thionyl chloride, heated to 70 ° C, react for 3 hours, distill under reduced pressure, and dry to obtain phenylalanyl chloride-s-triazine.
[0019] Example 2
[0020] To 20 mL of tetrahydrofuran solvent, add 16.5 mmol DL-phenylalanine, 33 mmol N,N-diisopropylethylamine, and 5 mmol cyanuric chloride, heat to 60 ° C in a nitrogen atmosphere, react for 18 hours, and distill under reduced pressure. The crude product is recrystallized from ethanol, and the crystalline product is added to 120 mmol thionyl chloride, heated to 60 ° C, react for 5 hours, distill under reduced pressure, and dry to obtain phenylalanyl chloride-s-triazine.
[0021] Example 3
[0022] Step (1), to 80mL N, N-dimethylformamide, add 16mmol triethylamine, 10mmol 4,4'-dihydroxydiphenyl sulfone, 6.7mmol phenylalanyl chloride-s-triazine (prepared by Example 1), stir and react for 18h at room temperature, then add 0.7mmol phenylalanyl chloride-s-triazine, react for 3h, add acetone to the solution, filter, wash with acetone, and dry to obtain acyl chloride-s-triazine diphenyl sulfone polymer.
[0023] Step (2), add 20 g of microcrystalline cellulose to 500 mL of N,N-dimethylformamide, stir, add 6 g of acyl chloride-s-triazine diphenyl sulfone polymer and 0.9 g of triethylamine, react at room temperature for 10 h, filter, wash with water and ethanol in turn, and dry to obtain modified cellulose.
[0024] Step (3), adding 2 kg of melamine resin and 0.4 kg of modified cellulose into an internal mixer, mixing at 75° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 165° C. for 5 min under 15 MPa to obtain a cellulose melamine resin composite material.
[0025] Example 4
[0026] Step (1), add 18mmol triethylamine, 10mmol 4,4'-dihydroxydiphenyl sulfone, 6.7mmol phenylalanyl chloride-s-triazine (prepared by Example 1) to 70mL N,N-dimethylformamide, stir and react for 18h at room temperature, then add 0.3mmol phenylalanyl chloride-s-triazine, react for 2h, add acetone to the solution, filter, wash with acetone, and dry to obtain acyl chloride-s-triazine diphenyl sulfone polymer.
[0027] Step (2), add 20 g of microcrystalline cellulose to 400 mL of N,N-dimethylformamide, stir, add 4 g of acyl chloride-s-triazine diphenyl sulfone polymer and 0.6 g of triethylamine, react at room temperature for 6 h, filter, wash with water and ethanol in turn, and dry to obtain modified cellulose.
[0028] Step (3), adding 2 kg of melamine resin and 0.55 kg of modified cellulose into an internal mixer, mixing at 80° C. for 30 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 160° C. for 5 min at 20 MPa to obtain a cellulose melamine resin composite material.
[0029] Example 5
[0030] Step (1), to 80mL N, N-dimethylformamide, add 15mmol triethylamine, 10mmol 4,4'-dihydroxydiphenyl sulfone, 6.7mmol phenylalanyl chloride-s-triazine (prepared by Example 1), stir and react for 24h at room temperature, then add 0.7mmol phenylalanyl chloride-s-triazine, react for 2h, add acetone to the solution, filter, wash with acetone, and dry to obtain acyl chloride-s-triazine diphenyl sulfone polymer.
[0031] Step (2), add 20 g of microcrystalline cellulose to 500 mL of N,N-dimethylformamide, stir, add 10 g of acyl chloride-s-triazine diphenyl sulfone polymer and 1.6 g of triethylamine, react at room temperature for 10 h, filter, wash with water and ethanol in turn, and dry to obtain modified cellulose.
[0032] Step (3), adding 2 kg of melamine resin and 0.7 kg of modified cellulose into an internal mixer, mixing at 70° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 150° C. for 8 min under 15 MPa to obtain a cellulose melamine resin composite material.
[0033] Example 6
[0034] Step (1), add 15mmol triethylamine, 10mmol 4,4'-dihydroxydiphenyl sulfone, 6.7mmol phenylalanyl chloride-s-triazine (prepared by Example 1) to 70mL N,N-dimethylformamide, stir and react for 24h at room temperature, then add 0.5mmol phenylalanyl chloride-s-triazine, react for 2h, add acetone to the solution, filter, wash with acetone, and dry to obtain acyl chloride-s-triazine diphenyl sulfone polymer.
[0035] Step (2), add 20 g of microcrystalline cellulose to 500 mL of N,N-dimethylformamide, stir, add 8 g of acyl chloride-s-triazine diphenyl sulfone polymer and 1.3 g of triethylamine, react at room temperature for 8 h, filter, wash with water and ethanol in turn, and dry to obtain modified cellulose.
[0036] Step (3), adding 2 kg of melamine resin and 0.8 kg of modified cellulose into an internal mixer, mixing at 80° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 15 MPa and 160° C. for 6 min to obtain a cellulose melamine resin composite material.
[0037] Comparative Example 1
[0038] Step (1), adding 2 kg of melamine resin into an internal mixer, mixing at 75° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 165° C. for 5 min under 15 MPa to obtain a melamine resin material.
[0039] Comparative Example 2
[0040] Step (1), adding 2 kg of melamine resin and 0.4 kg of cellulose into an internal mixer, mixing at 75° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 165° C. for 5 min under 15 MPa to obtain a cellulose melamine resin composite material.
[0041] Comparative Example 3
[0042] Step (1), to 80mL N, N-dimethylformamide, add 16mmol triethylamine, 10mmol 4,4'-dihydroxydiphenyl sulfone, 6.7mmol phenylalanyl chloride-s-triazine (prepared by Example 1), stir and react for 18h at room temperature, then add 0.7mmol phenylalanyl chloride-s-triazine, react for 3h, add acetone to the solution, filter, wash with acetone, and dry to obtain acyl chloride-s-triazine diphenyl sulfone polymer.
[0043] Step (2), adding 2 kg of melamine resin and 0.4 kg of acyl chloride-based s-triazine diphenyl sulfone polymer into an internal mixer, mixing at 75° C. for 60 min, discharging the material, ball milling the material, placing the material in a flat vulcanizer, and hot pressing at 15 MPa and 165° C. for 5 min to obtain a melamine resin composite material.
[0044] The bending properties of melamine resin composite materials are tested according to GB T 9341-2008 method. The impact properties are tested according to GB / T1043.1-2008 method.
[0045] 6 mg of the melamine resin composite material was weighed and placed in a thermogravimetric analyzer for thermal performance analysis in a nitrogen atmosphere with a heating rate of 10° C. / min and a test temperature of 20-800° C.
[0046] The test results are shown in Table 1.
[0047] Table 1: Performance Test
[0048]
[0049] T 5% is the thermal decomposition temperature when the mass loss is 5%. 10% is the thermal decomposition temperature when the mass loss is 10%. Weight is the mass remaining ratio at 800℃.
[0050] After testing, compared with comparative example 1, cellulose microcrystals were added to the melamine resin in comparative example 2. Due to the poor compatibility between the two, the dispersion of cellulose microcrystals in melamine resin was not good, resulting in poor reinforcement effect of cellulose microcrystals, and the increase in bending strength and impact strength of melamine resin material was small. 5% and T 10% There is a downward trend and the heat resistance decreases.
[0051] Compared with Comparative Example 1, the melamine resin of Comparative Example 3 is added with an acyl chloride-based s-triazine diphenyl sulfone polymer. The polymer contains a triazine structure and has good compatibility with the melamine resin containing a triazine structural unit. When added to the resin material, the effect on its bending strength and impact strength is small. In addition, the polymer contains a heat-resistant diphenyl sulfone structure, which is introduced into the resin material matrix to improve the T 5% , T 10% And quality surplus rate, heat resistance are significantly improved.
[0052] The cellulose microcrystals modified with triazine diphenyl sulfone polymers are added to the melamine resins of Examples 4-6. The diphenyl sulfone polymers containing triazine structures introduced into the cellulose microcrystals have good compatibility with the melamine resin containing triazine structural units, which improves the dispersibility of the cellulose microcrystals in the melamine resin, making the cellulose microcrystals play a good reinforcing role, and the bending strength and impact strength of the melamine resin material are significantly improved. In addition, the heat-resistant diphenyl sulfone structure is introduced, and the T 5% , T 10% The mass surplus rate also increases significantly, improving the heat resistance.
Claims
1. A method for preparing a cellulose melamine resin composite material, characterized in that: The preparation method comprises the following steps: Step (1), adding triethylamine, 4,4'-dihydroxydiphenyl sulfone, and phenylalanyl chloride-s-triazine to N,N-dimethylformamide, stirring and reacting at room temperature for 18-24 hours, then adding phenylalanyl chloride-s-triazine, reacting for 2-3 hours, adding acetone to the solution, filtering, washing, and drying to obtain a chloride-s-triazine diphenyl sulfone polymer; Step (2), adding microcrystalline cellulose to N,N-dimethylformamide, stirring, adding acyl chloride-s-triazine diphenyl sulfone polymer and triethylamine, filtering after reaction, washing, and drying to obtain modified cellulose; Step (3), adding melamine resin and modified cellulose in a mass ratio of 100:(20-40) into an internal mixer for mixing, discharging the material, ball milling the material, and placing the material in a flat vulcanizer for hot pressing to obtain a cellulose melamine resin composite material.
2. The method for preparing the cellulose melamine resin composite material according to claim 1, characterized in that: In the step (1), the molar ratio of triethylamine, 4,4'-dihydroxydiphenyl sulfone and phenylalanyl chloride-s-triazine is (1.5-1.8):1:(0.7-0.74).
3. The method for preparing the cellulose melamine resin composite material according to claim 1, characterized in that: In the step (2), the microcrystalline cellulose is stirred and then added with acyl chloride-based s-triazine diphenyl sulfone polymer and triethylamine in a mass ratio of 1:(0.2-0.5):(0.03-0.08).
4. The method for preparing the cellulose melamine resin composite material according to claim 1, characterized in that: The reaction in step (2) is carried out at room temperature for 6-10 hours.
5. The method for preparing the cellulose melamine resin composite material according to claim 1, characterized in that: In the step (3), the temperature during mixing in the internal mixer is 70-80° C. and the mixing time is 30-60 min.
6. The method for preparing the cellulose melamine resin composite material according to claim 1, characterized in that: In the step (3), the temperature during hot pressing in the flat vulcanizing machine is 150-165° C., the pressure is 15-20 MPa, and the time is 5-8 min.
7. The method for preparing the cellulose melamine resin composite material according to claim 2, characterized in that: The preparation method of the phenylalanyl chloride s-triazine comprises the following steps: adding DL-phenylalanine, N,N-diisopropylethylamine and cyanuric chloride to a solvent, heating to 60-85° C. in a nitrogen atmosphere, reacting for 12-18 hours, performing vacuum distillation, and recrystallizing, adding the crystallized product to thionyl chloride, heating to 60-70° C., reacting for 3-5 hours, performing vacuum distillation, and drying to obtain the phenylalanyl chloride s-triazine.
8. The method for preparing the cellulose melamine resin composite material according to claim 7, characterized in that: The solvent is tetrahydrofuran or 1,4-dioxane.
9. The method for preparing the cellulose melamine resin composite material according to claim 7, characterized in that: The molar ratio of DL-phenylalanine, N,N-diisopropylethylamine and cyanuric chloride is (3-3.3):(6-6.6):1.
Citation Information
Patent Citations
Environmentally friendly melamine powder material and preparation method thereof
CN113980421B
Melamine tableware and preparation method thereof
CN106519560A
Solid-solid phase change material based on cellulose acrylate and preparation method of solid-solid phase change material
CN108360080A
Preparation method of cellulose nano-whisker reinforced modified melamine molding compound
CN113429740A
Natural plant-based fiber and preparation method thereof
CN117845355A
Cited By
Melamine resin composite material with high heat resistance and preparation method thereof
CN120923964A
High-heat-resistant melamine resin composite material and preparation method thereof
CN120923964B